Diplomatie mit Gefühl. Vertrauen, Misstrauen und die Außenpolitik der Bundesrepublik Deutschland - Kreis, Reinhild 1978- (Zeitgeschichte im Gespräch, 2015)
Following the Second World War, Germany no longer enjoyed the trust of other nations. What did West Germany do to rebuild confidence? What was the role of trust, mistrust, and supervision during the East-West conflict as West Germany was integrated into the Western alliance, and how did they affect international relations between the two blocs? This study examines personal ties, rhetorical strategies, and institutional connections